Human red blood cell ATP content and export under hypoxic and/or isocapnic storage conditions - Chen, Youwei; Darrow, Cole; Murray, Aidan; Wise, Thomas; Li, Zhong Lucas; Srivastava, Nisha; Zhu, Hongmei; Welsby, Ian J.; Yoshida, Tatsuro; McMahon, Tim J. (Frontiers in Physiology, 2025)
IntroductionIn some diseases driving or associated with anemia, red blood cell (RBC) transfusion conveys limited benefit, and only when the anemia is severe. The banking of RBCs alters key molecules and functions. Among these changes during blood banking, depletion of the allosteric effector 2,3-BPG (biphosphoglycerate) takes place in the first two to 3 weeks, while ATP depletion only becomes prominent in the fifth or sixth (i.e., final) weeks of storage. One approach to testing the significance of these changes is to test the effects in vitro and in vivo of stabilizing key molecules. We hypothesized that hypoxic RBC storage, which can stabilize RBC BPG and ATP generation, could in turn stabilize the ability of RBCs to export vasoactive ATP, an activity that modulates RBC functions including O2 delivery.MethodsWe performed a parallel study of conventional RBCs, hypoxically stored (Hemanext) RBCs (“HN-Std RBCs”), and CO2-preserved, hypoxically stored RBCs (“HN + CO2 RBCs”).Results and discussionStandard hypoxic RBC storage boosted RBC ATP content, peaking in mid-storage. The time course of P50 (a measure of RBC Hb O2 affinity) changes in hypoxically stored RBCs corresponded to that of superior preservation of BPG, peaking in the first one to 2 weeks of storage. CO2-preserved hypoxic RBCs preserved ATP within the first week of storage, but with little effect on BPG or P50 at any time point. ATP export from RBCs assessed in normoxia or hypoxia declined over storage time, and generally did not differ significantly as a function of hypoxic storage ± CO2 preservation. An exception was the 1-week timepoint, when ATP export was significantly greater by HN + CO2 stored RBCs than by HN-Std stored RBCs. Taken together, these findings demonstrate time-dependent, differential modulation of RBC ATP and BPG by hypoxic RBC storage with or without CO2 preservation. Overall, hypoxic RBC storage ± CO2 preservation neither promotes nor restricts RBC ATP export to a large extent as compared to conventional RBC storage. Given that transfusion of hypoxically stored RBCs can be advantageous, future studies can test whether the differential and time-dependent effects on ATP, BPG and P50 can be leveraged for context-specific or personalized decision-making around RBC transfusion for anemia.